Micellar behavior of dodecyldimethylethyl ammonium bromide and dodecyltrimethyl ammonium chloride in aqueous media in the presence of diclofenac sodium - Mehta, S. K.; Bhasin, K. K.; Kumar, Anil; Dham, S. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
The micellar properties of cationic surfactants (S) viz. dodecyldimethylethyl ammonium bromide (DDAB) and dodecyltrimethylammonium chloride (DTAC) in aqueous media in the presence of diclofenac sodium (D) have been investigated by spectroscopic and conductivity measurements. The UV-vis and H-1 NMR studies suggest possible packing of diclofenac sodiurn molecules in the micelles. The conductivity studies were carried out over the temperature range 288.15-308.15 K. The critical micelle concentration (cmc) and degree of counterion binding (beta) of the micelles were determined at different temperatures. Delay in micellisation was observed for both DDAB and DTAC. Thermodynamic parameters (Delta G(m)(0) Delta H-m(0) and Delta S-m(0).) for the micelle system were estimated by applying the charged pseudo-phase separation model. The results of the ternary S/D/W system were analysed in comparison with the reported results of binary SAV system. The Delta G(m)(0) values for the ternary S/D/W system in both the cases show an increase in comparison to the respective binary SAV system. However, Delta S-m(0) decreased with temperature and remained positive in both the systems. At lower temperatures, the micellisation was found to be entropy-driven while at higher temperatures it was enthalpy-dfiven. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: diclofenac sodium; dodecyldimethylethylammonium bromide; dodecyltrimethylammoniurn chloride; Electrical conductivity; spectroscopic measurements

Insight into the micellization of dodecyldimethylethylammonium bromide (DDAB) in the presence of bovine serum albumin (BSA) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Journal of Colloid and Interface Science, 2008)
in this work, we report the effect of concentration of bovine serum albumin (BSA) on the micellization of a cationic surfactant, doclecyldimethylethylammonium bromide (DDAB). Several samples covering a wide range of concentrations of protein and surfactant have been investigated. The interactions between the moieties are investigated by measuring fluorescence quenching of BSA molecules. The aggregation number of DDAB micelles is found to be small in the presence of BSA. The formation of DDAB-BSA complex is confirmed by FTIR. Absorbance spectroscopy indicates that at higher concentration, the conformational stability of BSA in DDAB is higher. The viscosity data for protein-surfactant systems confirm conformational changes in protein chains induced by the surfactant. The cmc values for DDAB increase with increasing concentration of BSA. At higher temperatures the micellization-complexation becomes enthalpy-dominated. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: Aggregation number; BSA; conductivity; conformational stability; DDAB; FFIR; fluorescence; UV-visible; viscosity

Solubilization and conformational behavior of zein in aqueous solution of dodecyldimethylethylammonium bromide (DDAB) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2009)
The solubilization and conformational behavior of Zein in the presence of cationic surfactant, dodecyldimethylethylammonium bromide (DDAB) have been studied. The colloidal properties of DDAB in the absence and presence of Zein have also been investigated using physico-chemical and spectroscopy methods. The surfactant appears to bind to Zein at concentrations below the critical micelle concentration (cmc) and the binding becomes weaker at concentrations above the cmc. The interaction between DDAB and Zein depends on the chemical structure and molecular parameters (conformation, molar mass, charge) of the protein. The schematic sketches of the molecular mechanisms of the complex formation between like-charged proteins and surfactants have been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Absorbance spectroscopy; Aggregation number; conductivity; DDAB; FT-IR; Surface tension; viscosity; Zein